Combined impacts of warming and salinisation on trophic interactions and mortality of a specialist ephemeral wetland predator. (18th June 2019) - Cuthbert, Ross N.; Weyl, Olaf L. F.; Wasserman, Ryan J.; Dick, Jaimie T. A.; Froneman, P. William; Callaghan, Amanda; Dalu, Tatenda
Abstract: Wetlands are of enormous importance for biodiversity globally but are under increasing risk from multiple stressors driven by ongoing anthropogenic environmental change. As the trophic structure and dynamics of ephemeral wetlands are poorly understood, it is difficult to predict how these biodiverse ecosystems will be impacted by global change. In particular, warming and salinisation are projected to have profound impacts on these wetlands in future. The present study examined the combined effects of warming and salinisation on species interaction strengths and mortality rates for two ephemeral wetland species. Using an ephemeral pond specialist copepod, Lovenula raynerae Suárez‐Morales, Wasserman, & Dalu, (2015) as a model predator species, we applied a functional response approach to derive warming and salinisation effects on trophic interactions with a prey species. Furthermore, the effects of a salinisation gradient on mortality rates of adult copepods were quantified. The predatory copepod exhibited type II functional responses towards larval Culex pipiens mosquito prey, owing to high predation rates at low prey densities. Increased temperatures generally resulted in greater predator feeding rates, whilst increased salinities reduced consumption. However, the effects of temperature and salinity interacted: temperature effects on functional responses were suppressed under heightened salinities. Substantial mortality was observed in both male and female adult L. raynerae at salinity levels exceeding 10 parts per thousand. Warming and salinisation substantially altered interaction strengths in ephemeral wetland ecosystems, with implications for ecosystem function and stability. Furthermore, we demonstrated salinisation thresholds for mortality in an ephemeral wetland specialist, showing that salinisation may threaten the persistence of endemic species. The ongoing effects of warming and salinisation may therefore interact to alter trophic dynamics and species composition in ephemeral wetlands. These stressors should be considered synergistically within management practices.